SCIENTIFIC EVALUATION OF SIDDHA FORMULATION MUTHUCHIPPI PARPAM-A REVIEW - Velu Kanthal, *N. Senthil; Chithra, V; Rahul, V .A; Usha, S; gladys, R. Jeeva (International Journal of Ayurveda and Pharma Research, 2017)
The traditional Siddha system of medicine was made available to common people by saints of south India called as Siddhars. While the timeline of its origin seems to be unpredictable, this ancient medicine interrelates nature and human beings in terms of five basic elements or Pancha bootham viz, earth, water, fire, air and space. Presence of all these five basic elements in the human body and universe in a balanced proportion seem to govern the three vital humours of our body called Vatham, Pitham and Kapham. Any alterations in any of these humours is said to be the cause of Dosham or disease. Hence the Material Medica of this system consists of herbal origin(Mooligai), Mineral origin (Thathu) and animal origin of both land and ocean (Jeevam). According to the Siddha philosophy, these natural resources are the constitutions of these five basic elements and therefore have the ability to prevent and treat the Doshams (diseases) that are caused due to the altered humours. Parpam a potent Siddha formulation with a shelf life of 100 years is usually prepared by grinding mineral or animal sources with herbs followed by a process called Pudam(Incineration). Muthuchippi parpam (Calcinated shell of Pearl oyster) is one such drug of marine origin which has been indicated in the Siddha literature for a wide variety of diseases.This review article analysis the scientific facts behind the traditional use of Muthuchippi parpam.